Analysis of The Premarital Akken Tradition in Lampung Customary Culture from The Perspective of Islamic Law (A Case Study in Blambangan Village) - Yuli Ambar Wati; Ahmad Muslimin; Habib Sulthon Asnawi (Assyfa Journal of Islamic Studies, 2026)
The premarital akken tradition is a customary practice consistently maintained by the Lampung Pepadun community, particularly in Blambangan Village, North Lampung. This tradition serves as a mechanism for customary legitimation and social integration for cross-ethnic couples before the wedding contract. This study aims to examine the implementation, symbolic meanings, socio-cultural functions, and Islamic legal perspective on the akken tradition. A qualitative case study approach was employed. Data collection was conducted through observation, in-depth interviews with traditional leaders, religious figures, and community members, and documentation. The findings reveal that akken is performed through stages of customary consultation, deliberation, appointment of adoptive parents, and symbolic procession. This tradition embodies values of kinship, deliberation, respect for customs, and social responsibility. From the perspective of Islamic law, akken can be classified as 'urf shahih (valid custom) as it does not contradict scriptural texts and actually supports maqāṣid al-syarī'ah in preserving lineage and honor. This study concludes that akken represents a harmonious and adaptive integration of custom and sharia. Its main contribution is strengthening the theoretical framework of 'urf in the context of cross-cultural marriage in Indonesia.